Potentially toxic elements (PTEs) in the Carboniferous coal-bearing series of the Lublin Coal Basin (Poland), a case study - Ewa Krzeszowska (Case Studies in Chemical and Environmental Engineering)
During the coal mining process, large amounts of mining waste are produced and disposed of on the surface. This could result in significant quantities of toxic substances being released into the environment. The research material consisted of sedimentary rocks from the Lublin Coal Basin, which are potential waste geomaterial. The research included the chemical composition (SiO2, Al2O3, Fe2O3, CaO, Na2O, K2O, P2O5, MnO, TiO2, and Cr2O3 contents) obtained by XRF and the concentrations of potentially toxic elements (PTEs), such as As, Cd, Cu, Cr, Ni, Pb, and Zn, analyzed by ICP/MS The contents of total carbon and total sulfur obtained by the LECO analyzer. Furthermore, the article discusses the associations between toxic elements, as well as between toxic elements and Al, Si, (TOT/C), and (TOT/S). Analysis of potentially toxic elements (PTEs) as well as Fe concentrations revealed significant heterogeneity in the distribution of these elements in the vertical profile of the formation. The results indicated that the concentrations of toxic elements were As (1–25 ppm), Cd (0.1–0.3 ppm), Cu (2.1–77.9 ppm), Cr (21–179 ppm), Ni (11.2–230.1 ppm), Pb (10.0–52.8 ppm), and Zn (13–178 ppm). It was also found that PTEs concentrations are lower than the permissible values in soils, even in urban and recreational areas (in accordance with Polish legal standards). This indicates that the potential mining waste is not hazardous to the environment during its disposal or utilization.